Acute myocarditis triggering coronary spasm and mimicking acute myocardial infarction - Kumar, Andreas (Baishideng Publishing Group Inc, 2014)
A 24-year-old healthy man consulted to our center because of typical on-and-off chest-pain and an electrocardiogram showing ST-segment elevation in inferior leads. An urgent coronary angiography showed angiographically normal coronary arteries. Cardiovascular magnetic resonance imaging confirmed acute myocarditis. Although acute myocarditis triggering coronary spasm is an uncommon association, it is important to recognize it, particularly for the management for those patients presenting with ST-segment elevation and suspect myocardial infarction and angiographically normal coronary arteries. The present report highlights the role of cardiovascular magnetic resonance imaging to identify acute myocarditis as the underlying cause.